Echolocation and Stratum Preference: Key Trait Correlates of Vulnerability of Insectivorous Bats to Tropical Forest Fragmentation - Núñez, Silvia Fraixedas; López-Baucells, Adrià; Rocha, Ricardo; Farneda, Fábio Z.; Bobrowiec, Paulo E. D.; Palmeirim, Jorge M.; Meyer, Christoph F. J. (Frontiers in Ecology and Evolution, 2019)
Habitat loss and fragmentation rank high amongst the most pressing threats to biodiversity. Understanding how variation in functional traits is associated with species vulnerability in fragmented landscapes is central to the design of effective conservation strategies. Here, we used a whole-ecosystem ecological experiment in the Central Amazon to investigate which functional traits of aerial insectivorous bats best predict their sensitivity to forest fragmentation. During 2013 and 2014, bats were surveyed using passive bat recorders in six continuous forest sites, eight forest fragments, eight fragment edges, and eight forest clearings. The interaction between functional traits, environmental characteristics, and species distribution was investigated using a combination of RLQ and fourth-corner analyses. Our results showed that echolocation call structure, vertical stratification and wing aspect ratio were the strongest predictors of sensitivity to forest fragmentation. Frequency of maximum energy, body mass and relative wing loading did not show any correlation with the environmental traits. Bat species with constant-frequency calls were associated with high vegetation density, being more susceptible to forest fragmentation than species with frequency-modulated calls. Vertical stratum preference was also correlated with vegetation structure, indicating that understory species were more sensitive to forest loss than canopy species. Finally, species with high aspect ratio wings were linked to forest edges and clearings. Our findings suggest that species functional traits determine the vulnerability of aerial insectivorous bats towards fragmentation and, similarly, environmental conditions determine if a species is likely to become locally extinct due to fragmentation. Preserving structurally complex forests will be crucial to ensure the long-term persistence of the most sensitive and vulnerable species of this bat ensemble in fragmented landscapes across the Neotropics.